Alternative Forms of the Rey Auditory Verbal Learning Test: A Review - Keith A. Hawkins; David Dean; Godfrey D. Pearlson (Behavioural Neurology)
Practice effects in memory testing complicate the interpretation of score changes over repeated testings, particularly in clinical applications. Consequently, several alternative forms of the Auditory Verbal Learning Test (AVLT) have been developed. Studies of these typically indicate that the forms examined are equivalent. However, the implication that the forms in the literature are interchangeable must be tempered by several caveats. Few studies of equivalence have been undertaken; most are restricted to the comparison of single pairs of forms, and the pairings vary across studies. These limitations are exacerbated by the minimal overlapping across studies in variables reported, or in the analyses of equivalence undertaken. The data generated by these studies are nonetheless valuable, as significant practice effects result from serial use of the same form. The available data on alternative AVLT forms are summarized, and recommendations regarding form development and the determination of form equivalence are offered.